Harmonizing results of ataxia rating scales: mFARS, SARA, and ICARS. Issue 12 (16th November 2022) - Rummey, Christian; Harding, Ian H.; Delatycki, Martin B.; Tai, Geneieve; Rezende, Thiago; Corben, Louise A.
Abstract: The ever‐increasing body of ataxia research provides opportunities for large‐scale meta‐analyses, systematic reviews, and data aggregation. Because multiple standardized scales are used to quantify ataxia severity, harmonization of these measures is necessary for quantitative data pooling. We applied the modified Friedreich Ataxia Rating Scale (mFARS), the Scale for the Assessment and Rating of Ataxia (SARA), and the International Cooperative Ataxia Rating Scale (ICARS) to a large cohort of people with Friedreich's ataxia. We provide regression coefficients for scale interconversion and discuss the reliability of this approach, together with insights into the differential sensitivities of mFARS and SARA to disease progression.